Learning walks as a chance of reintegration for young offenders in three countries of Central Europe: Belgium, France, and Germany. (January 2021) - Koenig, Karsten; Knospe, Yvonne
Highlights: Learning walks with young offenders offers an alternative way back to society. During a long-distance-walk, participants have the chance to develop resilience. Learning walks are a solution to promote stress-reducing resources. The method supports resources like self-efficacy and positive self-concept. The method could focus more on methods of learning and professional training. Abstract: Delinquent behaviour is often an expression of the juvenile development phase, and at the same time a possible entry into criminal careers. Resilience is regarded as a protective factor and supports people in coping with their life tasks and challenges, and especially in the case of juvenile delinquents, their reintegration into society. We present the concept of distance walking as a socio-pedagogical method, and the available empirical material on walks and their results are analysed with respect to their contribution to the development of resilience. Theoretical concepts complete the explanation of the positive effect of resilience enhancement.